Preparation and characterization of bosentan monohydrate/ε‐polycaprolactone nanoparticles obtained by electrospraying. (8th December 2018) - Giménez, Virna M.; Sperandeo, Norma; Faudone, Sonia; Noriega, Sandra; Manucha, Walter; Kassuha, Diego
Abstract : The electrospraying technique provides nano and microparticles that can be used as drug delivery systems. The aims of this study were, firstly, to optimize the influent parameters of electrospraying for the manufacture of a Bosentan (BOS) nanoparticulate platform, and secondly, to evaluate its physicochemical properties and in vitro biopharmaceutical behavior. Particles were characterized by scanning electron microscopy (SEM), powder X‐ray diffraction (PXRD), differential scanning calorimetry (DSC), thermogravimetry (TG) and Fourier transformed Infrared spectroscopy (FTIR). Drug loading, encapsulation efficiency and kinetic dissolution were determined. Additionally, Bosentan release assays at 24 and 72 h were performed in vitro to evaluate biopharmaceutical properties of nano‐scaffolds by diffusion technique through dialysis bag. The nanostructures had heterogeneous sizes predominantly smaller than 550 nm and they were semicrystalline according to PXRD, indicating a partial amorphization of BOS during the encapsulation in the polymer matrix. FT‐IR and DSC showed an absence of chemical interactions between BOS and ε‐Polycaprolactone (PCL), suggesting that both components behaved as a physical mixture in these particles. The drug loading was 25.98%, and the encapsulation efficiency was 58.51%. Additionally, the release assays showed an extended and controlled release of BOS, in comparison to non‐encapsulated BOS. These data also showed to fit with the Cubic Root kinetic dissolution. As a conclusion, we demonstrate that the use of electrospraying for the manufacture of BOS (or similar drugs) controlled release nanoplatforms would represent an interesting contribution in the development of new therapeutic alternatives for the treatment of pathologies such as pulmonary hypertension and other related diseases . © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2748, 2019.